José Martí and his thinking in the sciences - Martínez-Prieto, Dalmis (2024)
If we delve into the conceptions of science and technology that José Martí bequeathed us, we appreciate that each of them has considered, in its historical moment, the significance it has for the development of society. The purpose of this article is to reflect, through a bibliographic review, on José Martí’s thinking in science, which includes his updated information and guiding dissemination of the advances in science and technology of his time and today. The objective of the work presented is to present a brief compilation of Martí’s thoughts in the sciences, demonstrating that the same line of thought exists. The materialist dialectic of Marxism-Leninism was assumed as the guiding method, using theoretical and empirical methods. The essential theoretical postulates are systematized that allow establishing fundamental concepts and theoretical positions, basing the lucidity and sensitivity of José Martí with respect to the paths of technological development of his time and environment, the ability to unravel truths, to make sense of things, in all the domains of knowledge he dealt with, stating that he was a man of science and that the validity of Martí’s scientific thought is increasingly greater in our times